Anaesthetic management of a patient with sub-valvular aortic stenosis for emergency lower segment caesarean section: A case report - Anita R Chhabra; Prajakta D Shinde; Vijay L Shetty; Atul M Ganatra (Wolters Kluwer Medknow Publications, 2022)
Sub-valvular aortic stenosis (SAS) occurs due to a fibrous membrane or a muscular narrowing causing left ventricular outflow tract obstruction. The physiological changes of pregnancy may exacerbate the cardiac condition posing significant challenges for anaesthesia and surgery. A 34 years primigravida, with 32 weeks gestation, a known case of sub-valvular aortic stenosis presented in the emergency room in view of leaking/bleeding per-vagina. Risk factors such as tachycardia, decrease in afterload, preload and increased left ventricle contractility lead to exacerbation of the obstruction and should be avoided. We report a successful anaesthetic management of her lower segment cesarean section while balancing the physiological changes of pregnancy superimposed by pathology of the disease.